Pengaruh Cita Rasa, Kualitas Produk dan Harga Terhadap Kepuasan Konsumen Mie Gacoan Tarum Barat-Bekasi - Aditya; Yanto Kamarudin (Publikasi Indonesia, 2025)
This research aims to analyze the influence of taste, product quality and price on consumer satisfaction with Mie Gacoan in West Tarum - Bekasi. The background to this research is based on the rapid development of culinary businesses in Indonesia, especially in Bekasi Regency, which offers a variety of noodle choices that are popular among the public. Mie Gacoan, as a restaurant that serves noodles with a choice of spiciness levels, has become a favorite among all groups and has affordable prices. The method this research uses is quantitative by collecting data through questionnaires to determine the relationship between the variables of taste image, product quality and price on consumer satisfaction. It is hoped that the results of the research will provide insight for culinary business actors in increasing mutual power and attracting more consumers through managing taste image, product quality and optimal prices.